2019
DOI: 10.7554/elife.42078
|View full text |Cite
|
Sign up to set email alerts
|

Timing mechanism of sexually dimorphic nervous system differentiation

Abstract: The molecular mechanisms that control the timing of sexual differentiation in the brain are poorly understood. We found that the timing of sexually dimorphic differentiation of postmitotic, sex-shared neurons in the nervous system of the Caenorhabditis elegans male is controlled by the temporally regulated miRNA let-7 and its target lin-41, a translational regulator. lin-41 acts through lin-29a, an isoform of a conserved Zn finger transcription factor, expressed in a subset of sex-shared neurons only in the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 90 publications
4
39
0
1
Order By: Relevance
“…Downstream of LIN41 in the heterochronic pathway, our results define the immediate next layer of regulatory function by identifying the relevant direct targets of LIN41 and their specific developmental roles. The results presented here and elsewhere (Pereira et al, 2019) demonstrate that lin-29a , mab-10 , mab-3 , and dmd-3 , previously shown to be directly, post-transcriptionally silenced by LIN41 (Aeschimann et al, 2017), act as the main regulatory output of the let-7 –LIN41 pathway in the J/A transition. Thus, despite other proposed molecular activities as an E3 ubiquitin ligase and a structural protein, the function of LIN41 as an RNA-binding protein accounts for its known heterochronic functions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Downstream of LIN41 in the heterochronic pathway, our results define the immediate next layer of regulatory function by identifying the relevant direct targets of LIN41 and their specific developmental roles. The results presented here and elsewhere (Pereira et al, 2019) demonstrate that lin-29a , mab-10 , mab-3 , and dmd-3 , previously shown to be directly, post-transcriptionally silenced by LIN41 (Aeschimann et al, 2017), act as the main regulatory output of the let-7 –LIN41 pathway in the J/A transition. Thus, despite other proposed molecular activities as an E3 ubiquitin ligase and a structural protein, the function of LIN41 as an RNA-binding protein accounts for its known heterochronic functions.…”
Section: Discussionsupporting
confidence: 76%
“…The C. elegans heterochronic pathway is arguably one of the best-characterized developmental timing pathways, and recent evidence has suggested that its function in controlling the onset of J/A transition might be evolutionarily conserved (Corre et al, 2016; Faunes & Larrain, 2016; Pereira et al, 2019). However, despite extensive knowledge of the genetic players and their relative positions in the heterochronic pathway, a detailed mechanistic concept is still lacking and requires better characterization of direct molecular connections among individual heterochronic genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, TRIM71 regulates proliferation and differentiation of human induced pluripotent and mouse neuronal stem cells (Chen et al 2012;Worringer et al 2014), limb development (Lancman et al 2005), and neurulation (Maller Schulman et al 2008) and is implicated in human congenital hydrocephalus (Furey et al 2018). In Caenorhabditis elegans, where TRIM71 is known as LIN-41, it controls differentiation and self-renewal of epidermal progenitor cells (Slack et al 2000), oocyte maturation (Spike et al 2014;Matsuura et al 2016), oocyte-toembryo transition (Tocchini et al 2014), reproductive organ formation (Del Rio-Albrechtsen et al 2006;Ecsedi et al 2015;Aeschimann et al 2019), and sexually dimorphic neuron differentiation (Pereira et al 2019). Trim71 overexpression is associated with rapid disease progression in myxoid liposarcoma (De Cecco et al 2014), hepatocellular carcinoma (Chen et al 2013), and nonsmall cell lung cancer (Ren et al 2018).…”
mentioning
confidence: 99%
“…In C. elegans , most of these differences arise during the fourth stage of larval development, just before they become sexually active, but how do cells know when to become different? Now, in eLife, Oliver Hobert of Columbia University and colleagues – including Laura Pereira as first author – report that the heterochronic pathway (which regulates the larval development of worms) is also involved in controlling the timing of sexual differentiation in the nervous system of C. elegans (Pereira et al, 2019).…”
mentioning
confidence: 99%